A hazai mezőgazdasági vállalkozások gazdálkodása, a belső felhalmozás, a hitelezés és a támogatási csatorna tükrében 2005 és 2014 között = The management of Hungarian agricultural enterprises in the light of the internal capital formation and the lending and state aid channels between 2005 and 2014 - Varga, József; Sipiczki, Zoltán (Közép-Európai Közlemények, 2017)
The study analyzes the Hungárián agricultural businesses in a financial point of view, based on the Agricultural Research Institute’s database. The analysis works with of the statistically closed 2005 - 2014 period. The article presents the important characteristics of the database. Then it includes a financial analysis based on index numbers, where particularly the relations of the scale of the size, the equity, the debt- and aid channels are analyzed. Finally the factors affecting lending are determined based on an empirical analysis. Efficiency improvement demands particularly high expenses in this sector. The article’s basic idea is that in the agriculture there is a close correlation between the three channels of financing: equity raising, lending and aid. However, these sources of funding operate in a hierarchy system. In our point of view, a considered agricultural financing system, needs to focusing on lending channel. This channel can organize the structure of agricultural production based on economic considerations.